Application of Traditional Japanese Drug Jidabokuippo in a Modern Society - Hajime Nakae; Yasuhito Irie; Toshiharu Kitamura; Manabu Okuyama (Frontiers Media S.A., 2022)
Background: Jidabokuippo (JDI) (治打撲一方) has been used in Japan to alleviate contusion-induced swelling and pain since medieval times.Method: This review investigated the effects of JDI on various symptoms in patients with trauma or static blood[TM1]. The PubMed and Igaku Chuo Zasshi databases were searched until 24 December 2021. We summarize the benefits of applying JDI to inflammatory conditions, including bruises.Results: JDI has been used to resolve blood [TM1] stasis, regulate qi in trauma patients, and treat inflammatory swelling and pain caused by rheumatoid arthritis and cellulitis. As the adverse event rate associated with JDI is low (1.3%), JDI is considered a safe drug.Conclusion: JDI can be used to resolve blood[TM1] stasis in trauma patients without adverse events associated with nonsteroidal anti-inflammatory drugs.